Mengatasi Penurunan Attention Span Mahasiswa Akibat TikTok dan Reels: Tinjauan Pustaka tentang Strategi Belajar Akademik - Aprima Fitria Candra; Desy Safitri; Sujarwo Sujarwo (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Attention span is a person’s ability to focus on a piece of information without being distracted for a certain period of time. This study aims to examine the learning strategies employed by university students to adress the decline in their attention span resulting from the use of TikTok and Reels. Using a literature study approach, data were collected from scientific journal articles and official websites discussing the use of short-form videos, attention apan among university students, and reccomended strategies for addressing attention span issues. The results of the study indicate that excessive consumption of short-form videos such as Tiktok and Reels can lead to a reduction in attention span, cognitive decline, and academic performance amongst students. Therefore, learning strategies such as setting learning goals and maintaining motivation, managing time through screen time management, using the pomodoro technique, and fostering concentration can be adopted by university students to adress issues with their attention span.